The manufacture and distribution temperature of aluminum molding for plastic beam from waste PP - H, Hendra; Putra, Yoga Rahmadi; Septiana, Reski; Hernadewita; Demustila, Harly; Rispandi; Hermiyetti; Rahmayetty (METAL: Jurnal Sistem Mekanik dan Termal, 2025)
One method utilized in the production of plastic goods is injection molding. An essential part of the injection molding process is a mold, which is used to create different types of plastic goods in accordance with a preset design. The goal of this study is to create plastic beam molding molds using the EDM and milling production methods and evaluate the molds' form geometry and resilience to temperature. The material's thermal conductivity is 200 W/m.k. due to the properties of the 1060 aluminum alloy. It can be determined that the low mold temperature during the injection process causes plastic products to distort and swell. The results show that the EDM machining technique achieved a frequency of 142.8% and a duty cycle value of 57%. Using barrel temperatures of 1600C and 250°C for temperature resistance tests, the mold was determined to be in rather good condition when exposed to high temperatures. This is demonstrated by the results of testing the shape's geometry, which showed similarity in the product's dimensions with the mold and an increase in the product's dimensions.